ENHANCING LOCAL HEALTHCARE DELIVERY: THE ROLE OF COMMUNITY PHARMACIES IN STRENGTHENING LOCAL SELF-GOVERNANCE AND PUBLIC HEALTH POLICY (Lex localis - Journal of Local Self-Government, 2025)
This review synthesizes 80 peer-reviewed studies to evaluate the pivotal role of community pharmacies in enhancing local healthcare delivery and strengthening local self-governance through public health policy integration. We explore global practices where pharmacies improve access to healthcare services, promote health education, and collaborate with local governments to implement policies at sub-national levels. Key themes include service accessibility, policy advocacy, and community engagement. Findings highlight pharmacies’ contributions to health equity and propose a multi-level framework for their integration into governance structures. This work offers actionable insights for policymakers to leverage pharmacies in sustainable local health systems.